Past simple - time expressions. - León Malavé, Juan Carlos (2023)
This research study for the practical component of the comprehensive examination is based on innovative strategies and approaches adapted to the large classes that disrupt the flow of classroom activities and interfere with learning in education nowadays. The study was carried out in the Unidad Educativa Americano, the 42 students study subjects belong to the 2nd level of high school parallel E; the learning content is related to the Simple Past - Time Expressions. However, observation would be crucial as a research tool, providing qualitative and descriptive data about anything that revealed an overview of the current state of the teaching-learning processes of English as a foreign language within this setting. In the English area, the purpose of this process is to evaluate the classroom management of teachers through an evaluation in an educational field to know and investigate the various shortcomings of a real situation, to reflect on it, and to be able to act accordingly to improve the learning.